An Efficient Evaluation System Accelerates α-Helical Antimicrobial Peptide Discovery and Its Application to Global Human Genome Mining - Liu, Licheng; Wang, Caiyun; Zhang, Mengyue; Zhang, Zixuan; Wu, Yingying; Zhang, Yixuan (Frontiers in Microbiology, 2022)
Antimicrobial peptides (AMPs), as an important part of the innate immune system of organism, is a kind of promising drug candidate of novel antibiotics due to their unique antibacterial mechanism. However, the discovery of novel AMPs is facing a great challenge due to the complexity of systematic experiment and the poor predictability of antimicrobial activity. Here, a novel and comprehensive screening system, Multiple Descriptor Multiple Strategy (MultiDS), was proposed based on 59 physicochemical and structural parameters, 3 strategies and 4 algorithms for the mining of α-helical AMPs. This approach was applied to mine the encrypted peptide antibiotics from the global human genome including introns and exons. A library of approximately 70 billion peptides with 15-25 amino acid residues was screened by the MultiDS system and generated a list of peptides with the Multiple Descriptor Index (MD index) scores, which was the core part of the MultiDS system. Sixty peptides with top MD scores were chemically synthesized and experimentally tested their antimicrobial activity against 10 kinds of Gram-positive bacteria, Gram-negative bacteria (including drug-resistant pathogens). Fifty-nine out of 60 (98.3%) peptides exhibited antimicrobial activity (MIC ≤ 64 μg/mL), and 24 out of 60 (40.0%) peptides showed high activity (MIC ≤ 2 μg/mL), validating MultiDS was an effective and predictive screening tool with high hit rate and superior antimicrobial activity. For further investigation, AMPs S1, S2 and S3 with the highest MD scores were used to treat the skin infection mouse models in vivo caused by Escherichia coli, drug-resistance Escherichia coli and Staphylococcus aureus respectively. All of S1, S2 and S3 showed comparable therapeutic effects on promoting infection healing to or even better than the positive drug levofloxacin. A mechanism study discovered the rapid bactericidal action was caused by cell membrane disruption and content leakage. The MultiDS system not only provides a high-throughput approach that allows for the mining of candidate AMPs from global genome sequence, but also opens up a new route to accelerate the discovery of peptide antibiotics.